Explicit and implicit attitudes towards people with intellectual disabilities: The role of contact and participant demographics. Issue 5 (23rd November 2017) - Murch, Aidan J.; Choudhury, Tanveen; Wilson, Michelle; Collerton, Eleanor; Patel, Maya; Scior, Katrina
Abstract : Background: Intellectual disability research has concentrated on self‐reported explicit attitudes with little focus on implicit attitudes. Such attitudes are evaluations which occur with or without conscious awareness, respectively. This investigation examined participants' (N = 234) attitudes towards individuals with intellectual disabilities with reference to participants' gender, age, level of education, frequency of contact and closeness. Method: UK adults completed explicit (ATTID) and implicit attitude (ST‐IAT) measures, and provided demographics via an online survey. Results: Participant demographics predicted explicit attitudes—with differing cognitive, affective and behavioural associations. Contact frequency was most significant. Implicit attitudes were not predicted, evidencing implicit–explicit attitude differences. Conclusions: The results encourage more implicit–explicit attitude relationship research regarding disability. The associations between demographics, contact and implicit attitudes should be explored further. Research should question whether implicit attitudes reflect participants' true beliefs—denoting less importance to demographics—or whether they reflect wider societal values rather than individuals' attitudes.